Biodegradable stent for the treatment of a colonic stricture in Crohn's disease - Rodrigues, C (2013)
Biodegradable polydioxanone stents were developed for the treatment of refractory benign esophageal strictures but have been suggested as a new therapeutic option for intestinal strictures. The primary advantage of biodegradable stents over self-expandable metallic stents is that removal is not required. There are, however, few data available on their use in the small or large bowel. We herein describe the case of a 33-year-old patient with long-standing Crohn's disease (CD) who developed a fibrotic stricture of the sigmoid too long to be amenable to balloon dilation. The use of a biodegradable polydioxanone stent was chosen to avoid surgery. Combined endoscopic and fluoroscopic placement of the stent was technically simple, safe and clinically successful, and no recurrence of obstructive symptoms occurred during a 16-mo follow-up. Further studies are needed to evaluate the long-term efficacy and safety of biodegradable stents in the treatment of intestinal strictures, particularly in the context of CD.